The influence of Muslim fashion bloggers on young Muslim females‘ fashion and life in Malaysia. - Mohd Zaimmudin Mohd Zain (2020)
Originating as a hobby to journalise one‘s daily routine, fashion blogging has evolved to become an important fashion reference source, medium for fashion engagement, and fashion marketing tool (Rocamora, 2011; Esteban-Santos et al., 2018). Moreover, the fashion bloggers‘ roles have evolved to becoming fashion opinion leaders with the ability to persuade followers to buy or adopt their fashion style (Casalo et al., 2018). This study explores the influences of fashion bloggers in a Muslim context where religious norms restrict females‘ ability to engage fully with fashion trends. Religion has an impact on choosing apparel or fashion products among Muslim fashion consumers (Alam et al., 2011; Aliman et al. 2018) along with culture (Almila, 2016). Young Muslim female fashion consumers in Malaysia are currently showing interest in Western fashion styles, but at the same time, they must adhere to Muslim values regarding appropriate dress. Hence, they need trustworthy sources for style ideas that minimise the social risk of consuming something inappropriate or seek advice regarding this emerging fashion among Muslim consumers, particularly fashion bloggers. This study takes a qualitative approach (netnography and interviews). Netnography data was gathered from the comment threads of two Muslim female fashion bloggers‘ Instagram account over three months alongside interview data from 16 Muslim female fashion consumers in Malaysia. This study has contributed to the emerging literature on mediation between Islamic and Western trends that enables Muslim consumers to choose the balance between Islamic and Western in their everyday practice, despite the possible conflict of ideas on both elements. Moreover, this study has also extended the emerging literature on the influence of fashion bloggers as credible fashion sources, that fashion bloggers are the mediating factor to reconcile and legitimise the combination of Islamic and Western styles. This study also extends the literature on the impact of fashion opinion leadership and the credibility of fashion bloggers. Fashion bloggers also become the inspiration for fashion because they can avoid the risk of choosing inappropriate fashion products for Muslim fashion consumers. At the same time, good manners are the new finding for additional credibility that they are looking for in fashion bloggers. Moreover, this finding contributes and extends the emerging literature on the fashion social media that Muslim consumers are using Instagram to look for modest and modern style.